The Social and Educational Implications of Digital Governance in the Western Balkans - Beleraj, Iris; Stefani, Edvin (European Journal of Social Science Education and Research, 2026)
This research investigates the social and educational implications of digital governance policies within the six Western Balkan countries: Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia, and Serbia. Utilizing a mixed-methods approach, this study analyzes how e-government initiatives impact social inclusion, digital literacy, workforce education, and gender equality from 2020 to 2025. Findings reveal varied progress in digital transformation across the region, with some countries demonstrating advanced digital infrastructure while others face significant challenges in ensuring equitable access and digital skills development. The study highlights persistent obstacles such as digital divides, cybersecurity vulnerabilities, and insufficient resources that impede the full realization of social and educational benefits. This research contributes to the understanding of digital governance in transitional economies, offering insights for policymakers to foster inclusive digital transformation and address social inequalities in the Western Balkans.